Computional analysis of connecting rod / Mohd KhairuI Hafiz Rusli and Mohd Arif Jani - Rusli, Mohd KhairuI Hafiz; Jani, Mohd Arif (2005)
Computional analysis of connecting rod is a method that we are analysis of connecting rod and find the information from solid work software. Typically, three result of analysis are used: 1. Stress result 2. Displacement result 3. Deformation result For our project, we have studied about this method and try to apply it by using data that we have collect from the real product. From these data we draw in solid work and find the analysis from using a cosmos express. We also learn how to draw in this software and get more knowledge from doing this project. COSMOSXpress design analysis results are based on linear static analysis and the material is assumed isotropic. Linear static analysis assumes that: 1) the material behavior is linear complying with Hooke’s law, 2) induced displacements are adequately small to ignore changes in stiffness due to loading, and 3) loads are applied slowly in order to ignore dynamic effects.